Improvements in Minimising Delays in Terrestrial Viaducts Construction for The RTS Link Project - Tasripan, Muhammad Akram; Ganasan, Reventheran; Shafie, Rahimi (Progress in Engineering Application and Technology, 2023)
Nowadays, there has been rapid growth in the development of various critical infrastructure projects that aimed to support the country's economic growth. One such vital infrastructure component is the railway project. Railway projects offer numerous benefits to the public, including efficient transportation, alleviation of traffic congestion, improved accessibility and connectivity, and driving overall economic development. Any delays encountered during the construction, particularly in the viaducts phase, can disrupt the project timeline, resulting in increased expenditures and giving rise to various social challenges. Therefore, it is important to prevent this problem from occurring by identifying the causes and factors contributing to the delay of the terrestrial viaduct construction projects, analyse the effect of delays in the terrestrial viaduct construction and propose the methods that can be used to minimize or overcome the delay of the terrestrial viaduct construction especially for RTS Link project. To collect data for this study, a questionnaire was developed to analyze all the objectives. The questionnaire items were primarily adapted and modified from previous studies. To ensure heterogeneity in the survey responses and better understand, three distinct groups of respondents were targeted: clients, consultants, and contractors. The collected questionnaire data then was processed using the RII (Relative Importance Index) method to determine the relative importance of the identified causes and effects of delay in the research. Based on the result, the highest to the lowest ranked for all the causes, effects and methods to minimize or overcome the delay based on the survey has been identified. The explanation for the data obtained then being tabulated for further analysis. Overall, the results revealed that change orders/ additional works during construction works were the most common cause of delays. Next, cost and time overrun were the most common effects of delays and lastly, efficient communication and collaboration were found to be the most effective method in minimizing construction delays.